Is Positron Emission Tomography Reliable to Predict Post-Chemotherapy Retroperitoneal Lymph Node Involvement in Advanced Germ Cell Tumors of the Testis? - Akbulut, Ziya; Canda, Abdullah Erdem; Atmaca, Ali Fuat; Caglayan, Alper; Asil, Erem; Balbay, Mevlana Derya (Urology Journal, 2011)
<!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE FA <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Purpose: To evaluate if 18 fluorodeoxyglucose positron emission tomography (18FDG-PET) scan could identify post-chemotherapy retroperitoneal lymph node (RPLN) involvement in advanced germ cell tumors of the testis. Materials and Methods: Between January 2005 and January 2009, 16 patients with advanced germ cell tumors of the testis underwent RPLN dissection (RPLND) following chemotherapy. Before RPLND, abdominal computed tomography (CT), magnetic resonance imaging (MRI), and 18FDG-PET were performed in all the patients. Findings on 18FDG-PET were compared with pathological evaluation of the removed lymphatic tissue. Results: Both abdominal CT and MRI demonstrated retroperitoneal masses in all the patients following chemotherapy. Although PET did not demonstrate any activity in 8 patients, tumor was detected histopathologically. In 1 patient, 18FDG-PET demonstrated activity; however, no tumor was detected on pathology. Of the remaining 7 patients, 18FDG-PET findings were concordant with the histopathological findings. No activity was detected in 2 patients with no tumors whereas all 5 patients harboring viable tumor cells showed positive 18FDG-PET activity. In our study, sensitivity and specificity of 18FDG-PET in detecting RPLN involvement were detected to be 39% and 67%, respectively. Conclusion: 18FDG-PET imaging does not seem to be a reliable method in detecting RPLN involvement in advanced germ cell tumors of the testis following chemotherapy. Therefore, we neither recommend routine use of 18FDG-PET scanning nor decide the treatment work-up by solely relying on the 18FDG-PET findings in this patient group.